Generalized anxiety and bullying explanatory model as non-suicidal self-harm predictors in Peruvian adolescents - Jonatan Baños-Chaparro (Medisur)
Background: non-suicidal self-harm has been considered a public and social health problem during the last decade, which affects adolescents to a greater extent. Generalized anxiety and bullying can be trigger factors for its development. Objective: to analyze a generalized anxiety and bullying explanatory model as non-suicidal self-harm predictors in Peruvian adolescents. Methods: cross-sectional, explanatory design study, with 1,249 Peruvian adolescents, average age 15 years old (standard deviation = 1.49), who answered scales on generalized anxiety, bullying, and non-suicidal self-harm. For data analysis, statistical power, correlation, and a structural regression model based on covariances were applied to confirm the explanatory model. Results: the psychological variables were positively and statistically significantly correlated. The proposed model had adequate fit indices (CFI = 0.94; RMSEA = 0.03 [90% CI: 0.02-0.03] and SRMR = 0.04) and it was evidenced that generalized anxiety (β = 0.26, p = 0.001) and bullying dimensions such as aggression (β = 0.25, p = 0.001) and victimization (β = 0.21, p = 0.003) statistically significantly predicted self-harm not suicidal. Conclusions: The findings suggest that both generalized anxiety and bullying predict non suicidal self-harm in adolescents. The evidence provides useful information for developing and evaluating prevention programs based on these psychological variables, to reduce the non-suicidal self-harm risks.